The amazon várzea The decade past and the decade ahead - Pinedo-Vasquez, Miguel; Rufino, Mauro L.; Padoch, Christine; Brondizio, Eduardo S. (Springer Netherlands Imprint: Springer, 2011)
This book takes a multi-disciplinary and critical look at what has changed over the last ten years in one of the world's most important and dynamic ecosystems, the Amazon floodplain or várzea. It also looks forward, assessing the trends that will determine the fate of environments and people of the várzea over the next ten years and providing crucial information that is needed to formulate strategies for confronting these looming realities. The volume includes the latest research and analysis from a broad range of scientists who know the várzea best. It is dedicated to the memory of José Márcio Ayres, one of Brazil's greatest natural scientists and a pioneer in várzea research and conservation.